Evaluation of the Relationships Between Microbiota and Metabolites in Soft-Type Ripened Cheese Using an Integrated Omics Approach - Unno, Ryosuke; Suzuki, Toshihiro; Matsutani, Minenosuke; Ishikawa, Morio (Frontiers in Microbiology, 2021)
Cheese ripening is effected by various microorganisms and results in the characteristic flavors of cheese. Owing to the complexity of the microbiota involved, the relationship between microorganisms and components during ripening remains unclear. In this study, metagenomics and metabolomics were integrated to reveal these relationships in three kinds of surface mold-ripened cheeses and two kinds of bacterial smear-ripened cheeses. The microbiota is broadly divided into two groups to correspond with different cheese types. Furthermore, surface mold-ripened cheese showed similar microbiota regardless of the cheese variety, whereas bacterial smear-ripened cheese showed specific microbiota characterized by marine bacteria (MB) and halophilic and alkaliphilic lactic acid bacteria for each cheese variety. In the metabolite analysis, volatile compounds suggested differences in cheese types, although organic acids and free amino acids could not determine the cheese characteristics. On the other hand, Spearman correlation analysis revealed that the abundance of specific bacteria was related to the formation of specific organic acids, free amino acids, and volatile compounds. In particular, MB was positively correlated with esters and pyrazines, indicating their contribution to cheese quality. These methodologies and results further our understanding of microorganisms and allow us to select useful strains for cheese ripening.